Jane Tolmach Campaign Statement
This campaign statement outlines Jane Tolmach's positions in her 1976 race for the 36th Assembly District, emphasizing independence from special interests and strong advocacy for Ventura County. She prioritizes comprehensive tax reform focused on relieving local property taxpayers, making the system more progressive, reducing bureaucratic waste, and fully implementing the Serrano decision to equalize school funding. Tolmach strongly supports establishing a four-year state university in Ventura County and calls for careful reform of medical malpractice law and public sector labor relations, including limited support for binding arbitration and structured impasse procedures. She opposes Proposition 13 (dog racing), supports farmworkers' rights while reserving judgment on Proposition 14 pending further review, and declines to prejudge the LNG issue due to her City Council role. Overall, she frames tax reform as the most pressing legislative issue and presents herself as an experienced, pragmatic leader committed to fair representation and fiscal responsibility.